Age, gender and sociodemographic differences in school entrants' social and emotional competence - Nelson, Helen (Curtin University, 2012)
Aim. This research aimed to establish baseline age, gender, and sociodemographic differences in school entrants’ social and emotional competence to provide an empirical base for supporting positive responses to normal development in children as they begin school, thereby promoting life-long patterns of health and wellbeing. Review of Literature. Health priorities for children in a rapidly changing society are shifting due to the changing nature of social and emotional demands, resulting in an increasing complexity of health and developmental problems. Consequently, the role of the school nurse in primary and secondary schools is expanding, with a growing focus on providing support and early interventions for social, emotional, and behavioural issues. Bullying peaks at school entry and is associated with poor outcomes of health and education for children. Supporting the development of empathy in school-aged children has been proposed as a potential solution to the problem of bullying, but pathways of normal development of empathy and aggression are uncertain.Method. A cross-sectional observational study was conducted using a number of reliable and valid child and teacher questionnaires. Participants comprised a sample of children across Pre-primary, Year One and Year Two classes in an independent school. Statistical analysis was conducted using bivariate analyses and linear regression.Results. Teacher reported aggression was lower with age as empathy was higher, and girls were more empathic than boys. The higher level of reported empathy was not progressive, rather it occurred between Year One and Year Two, whereas aggression was not significantly lower between Year One and Year Two. There was no gender difference in teacher reported total aggression or covert aggression, and covert aggression was not reported to be higher with age.Discussion. In the first years of school, aggression lessens while empathy increases indicating that prosocial behaviour is a developmental milestone. Because of this, school nurses must understand the importance of surrounding children with safety in relationships as they begin school; in so doing, supporting developmental pathways of protection.